2023
DOI: 10.1039/d3nr00087g
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the energy transfer in Ruddlesden–Popper perovskites phases through isopropylammonium addition – towards efficient blue emitters

Abstract: Metal halide perovskites are hot contenders for the next generation of light emitters. Bright and colour-pure light-emitting diodes (LEDs) were demonstrated based on bulk 3D, nanocrystals, and quasi-2D structures (Ruddlesden-Popper...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 70 publications
0
2
0
Order By: Relevance
“…46,47 More recently, some of us have reported that the addition of isopropylammonium to (PEA) 2 (Cs 0.75 MA 0.25 )Pb 2 Br 7 is capable of blocking energy transfer to phases with n > 3 by changing the texture of the perovskite film. 48 Having established that the crystallization mechanism is strongly affected by the addition of NH 4 SCN as well as the stoichiometry of the precursor solution, we then proceeded to investigate the optical properties of our films using absorption and PL spectroscopy. The 3D and ⟨n⟩ = 20 films show a clear absorption onset corresponding to the band-gap energy of MAPbI 3 around 1.58 eV, indicating the dominance of 3D or 3D-like perovskite phases in these films (Figure 4a).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…46,47 More recently, some of us have reported that the addition of isopropylammonium to (PEA) 2 (Cs 0.75 MA 0.25 )Pb 2 Br 7 is capable of blocking energy transfer to phases with n > 3 by changing the texture of the perovskite film. 48 Having established that the crystallization mechanism is strongly affected by the addition of NH 4 SCN as well as the stoichiometry of the precursor solution, we then proceeded to investigate the optical properties of our films using absorption and PL spectroscopy. The 3D and ⟨n⟩ = 20 films show a clear absorption onset corresponding to the band-gap energy of MAPbI 3 around 1.58 eV, indicating the dominance of 3D or 3D-like perovskite phases in these films (Figure 4a).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The mixture of different perovskite phases in 2D/3D films constitutes an inhomogeneous energetic landscape in which energy is typically found to funnel from high-band-gap to low-band-gap phases, from which an efficient radiative recombination of charge carriers then takes place. Several reports have demonstrated the importance of crystallization dynamics by noting that the energetic landscape is sensitive to the choice of the organic spacer cation, solvent, , and deposition process . Even the stoichiometry of the precursor solution and variations in the ligand concentration across neighboring phases can change the photophysics of 2D/3D systems considerably. , More recently, some of us have reported that the addition of isopropylammonium to (PEA) 2 (Cs 0.75 MA 0.25 )­Pb 2 Br 7 is capable of blocking energy transfer to phases with n > 3 by changing the texture of the perovskite film . Having established that the crystallization mechanism is strongly affected by the addition of NH 4 SCN as well as the stoichiometry of the precursor solution, we then proceeded to investigate the optical properties of our films using absorption and PL spectroscopy.…”
Section: Resultsmentioning
confidence: 99%